2021
DOI: 10.37871/jbres1343
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, and Practices of Community Pharmacists on Antibiotic Resistance and Antimicrobial Stewardship in Lusaka, Zambia

Abstract: Background: Antimicrobial/Antibiotic Resistance (AMR) is among the major threats to global health. Due to limited information on the subject matter in Zambia, we assessed the knowledge, attitude, and practices of community pharmacists on AMR and Antimicrobial Stewardship (AMS). Materials and Methods: We conducted a descriptive cross-sectional study among 144 randomly selected community pharmacists through a structured questionnaire. Data were analysed using Statistical Package for Social Sciences version 22 a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 107 publications
0
3
0
Order By: Relevance
“…Lusaka district was purposively selected because it had the largest number of poultry farmers at the time of the study [ 41 ]. Moreover, this district currently has most of the community pharmacies in Zambia [ 119 , 120 ]. Poultry farmers accessed most of the poultry antibiotics in community pharmacies and agrovets [ 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…Lusaka district was purposively selected because it had the largest number of poultry farmers at the time of the study [ 41 ]. Moreover, this district currently has most of the community pharmacies in Zambia [ 119 , 120 ]. Poultry farmers accessed most of the poultry antibiotics in community pharmacies and agrovets [ 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…In Zambia, there is a paucity of information about the prescribing patterns of antibiotics based on the AWaRe classification. However, studies done in community pharmacies have reported increased dispensing of antibiotics without using prescriptions [18,56,57]. Therefore, it is against this background that the present study assessed the prescribing patterns of antibiotics according to the WHO AWaRe classification during the COVID-19 pandemic at the University Teaching Hospital (UTH) in Lusaka, Zambia.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, many pharmacies in Lusaka provide healthcare services to the communities. 105 The national population of Zambia is agglomerated essentially around Lusaka Province in the south and Copperbelt Province in the North, the two core economic hubs of the country. 119 With a total area of 21 896 km 2 , Lusaka Province is Zambia’s smallest province but the most densely populated and urbanized province.…”
Section: Methodsmentioning
confidence: 99%